2008
DOI: 10.1152/jn.00826.2007
|View full text |Cite
|
Sign up to set email alerts
|

Early Defects of GABAergic Synapses in the Brain Stem of a MeCP2 Mouse Model of Rett Syndrome

Abstract: Rett syndrome is a neurodevelopmental disorder caused by mutations in the transcriptional repressor methyl-CpG-binding protein 2 (MeCP2) and represents the leading genetic cause for mental retardation in girls. MeCP2-mutant mice have been generated to study the molecular mechanisms of the disease. It was suggested that an imbalance between excitatory and inhibitory neurotransmission is responsible for the behavioral abnormalities, although it remained largely unclear which synaptic components are affected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(190 citation statements)
references
References 56 publications
6
180
1
2
Order By: Relevance
“…An epigenetic study in a mouse model of RTT indicates that GABA A R ␤3 subunit expression is reduced in the cerebellum, and another molecular study confirmed down-regulation of the ␤3 subunit in the cerebellum (12,36). The ␣1 subunit in the frontal cortex and the ␣2 and ␣4 subunits in the ventrolateral medulla were also reduced in Mecp2-null mice (25). In LC neurons, our previous studies have shown that the postsynaptic GABA A and GABA B currents are both defective in Mecp2-null mice (10).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…An epigenetic study in a mouse model of RTT indicates that GABA A R ␤3 subunit expression is reduced in the cerebellum, and another molecular study confirmed down-regulation of the ␤3 subunit in the cerebellum (12,36). The ␣1 subunit in the frontal cortex and the ␣2 and ␣4 subunits in the ventrolateral medulla were also reduced in Mecp2-null mice (25). In LC neurons, our previous studies have shown that the postsynaptic GABA A and GABA B currents are both defective in Mecp2-null mice (10).…”
Section: Discussionmentioning
confidence: 94%
“…In mice, this is associated with multiple RTT-like phenotypes, including progressive motor dysfunction and abnormal breathing (15). In GABAergic neurons, impaired GABA synthesis and the consequent reduction in GABA quantum release have been found (10,15,25). In postsynaptic cells, there is a marked reduction in GABA A R density in the brain of RTT patients and Mecp2-null mice (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Medrihan et al (11) examined GABA synapses in the ventrolateral medulla of Mecp2 null males at postnatal day 7. Neither the discharge pattern relative to PN nor markers to more clearly define the area under study were used.…”
Section: Insufficient Gaba a Inhibition Underlies Tonic Activity In Ementioning
confidence: 99%
“…It is thus possible that de-regulated mTOR might adversely affect GABAergic synaptic activity. Notably, abnormal GABAergic transmission has been observed in Fmr1 knockout (KO) mice [134][135][136] and MeCP2 null mice [137,138]. In particular, Fmr1-KO mice have enhanced GABA-mediated synaptic transmission [134], while GABAergic synaptic transmission is greatly reduced in MeCP2 deficient mice [137,138].…”
Section: De-regulated Mtor Dendritic Spines and Synaptic Transmissionmentioning
confidence: 99%